Risk-Based Authentication using Autoencoders - Sharma, Bharat; Singh, Sidharth (International Journal of Computer Sciences and Engineering, 2019)
Verification gives a way to check the authenticity of a client attempting to get to any classified or delicate data. The requirement for ensuring secure information facilitated on the web has been rising exponentially as associations are moving their applications on the web. Static techniques for validation can`t totally ensure the validity of a client. This has prompted the advancement of multifaceted validation frameworks. Risk-based validation; a type of multifaceted verification adjusts as per the risk profile of the clients. This paper advances the plan of risk motor incorporated with the framework to inspect the client`s past login records and produce an appropriate example utilizing AI calculations to figure the risk dimension of the client. The risk level further chooses the confirmation technique that the client will be tested with. In this manner the versatile verification model aides in giving a more elevated amount of security to its clients.